Pencegahan Fraud Dengan Pengendalian Internal Dalam Perspektif Alquran - Eko Sudarmanto; Citra Kharisma Utami (Jurnal Ilmiah Ekonomi Islam, 2021)
The losses of fraudulent practices that are still occurring have become a problem for organizations and society today. The problem discussed in this study is limited fraud prevention with internal control seen from the perspective of the Qur’an, which is a holy book and the highest source of law for Moslems. This research is important to know how the perspective of the Qur'an in seeing and providing solutions to existing problems. The aim of this multi-case qualitative research is to explore methods of prevention against fraud by applying internal controls from the perspective of the Qur'an. As a conclusion, that internal control is part of corporate governance, so that management must consider the factors of thought, emotion, age, loyalty, justice, and the socio-economic environment of employees in formulating a policy. Internal controls need to be designed to be able to anticipate and prevent fraud that involves colluding with others. Internal controls can increase the ability to detect fraud by increasing effectiveness and utilizing the latest technology. Contextually, several principles in internal control are contained in several verses in the Qur’an. And what is more important is that in offering a solution to a problem, the Qur’an always provides a perspective not only materially but also spiritually.